Student Assistance ln Learning Applied Mathematics Entrepreneurship Concepts in The Creative Industries - Anwar, Muhammad Saidun; Choirudin, Choirudin; Manasikana, Arina; Astuti, Tiwi; Harliansyah, Faizuddin; Mastur; Huzaini, Huzaini (CV. Edutechnium Indonesia, 2023)
The low competence and power competitive graduates of college make Power absorb graduates in the field also low. As a result, many unemployed educated in various difficult areas get jobs. Importance of cultivating an entrepreneurial mentality for internalized students in frequent education called with edu-preneurship, Edupreneurship want to put concepts and attitudes entrepreneurship in the world of education. This thing took off from the reality trend of the graduate of College to look for work, not create field jobs. It's here thread red between education with entrepreneurship For change mindset and paradigm think students so that will appear to characteristics entrepreneurs like creativity, independence, and abstinence give up. Apart from believing in themselves, students must have a character that is task and result-oriented, that is is attitude trustworthy in operating work so that the result will satisfying. Executed processes and tasks with good and full trust, will give good results and assessments too. Character entrepreneur The other is brave take risk love challenge, and have soul leadership. Mentality and attitude Leadership is very important to be able to communicate, capable make planning, management, and evaluation with OK, as well Like for suggestions and constructive criticism. This character will make students have attitudes future-oriented, which means visionary and has perceptions and methods good view for the future.